Analysis of dental homologies and phylogeny of Paucituberculata (Mammalia: Marsupialia) - Abello, María Alejandra (2013)
The Paucituberculata is an endemic group of South American marsupials, recorded from the early Cenozoic up to the present. In this report, the most comprehensive phylogenetic analysis of Paucituberculata to date is presented. Fifty-seven terminal species were scored for 74 new and re-examined characters. Homologies of dental characters used in previous systematic studies were critically reviewed to evaluate their inclusion in the analysis. Phylogenetic results corroborated two major paucituberculatan clades, Palaeothentoidea and Caenolestoidea, and the main palaeothentoid groupings: Pichipilidae, Palaeothentidae, and Abderitidae. Taxon sampling and reinterpretations of molar cusp and crest homologies played an important role in the generation of new phylogenetic hypotheses. The main differences with respect to previous phylogenies were focused on palaeothentoid relationships: Palaeothentes boliviensis and Pilchenia lucina are not members of Palaeothentidae but instead clustered with Pilchenia intermedia and P. antiqua, forming the sister-group of a Palaeothentidae+Abderitidae clade, and Titanothentes simpsoni, previously considered a palaeothentine, is nested within the Acdestinae clade. Based on the time-calibrated phylogeny, the following stages in the paucituberculatan evolutionary history are suggested: origin of the group, in the Paleocene to early Eocene at the latest, split of Caenolestoidea and Palaeothentoidea clades during the late early to middle Eocene, evolutionary radiation of palaeothentid and abderitid lineages near the Oligocene-Eocene boundary, and decreased diversity and extinction of palaeothentoids during the middle Miocene.